Wyniki dziesięcioletniej obserwacji narządu wzroku u wcześniaków - Kubatko-Zielińska, Anna; Kobylarz, Joanna; Piwowarczyk, Anna; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: 1. To compare the incidence of refractive errors and the orthoptic condition in ten-year-old children, born prematurely and treated with cryotherapy versus children, whom did not apply such a procedure. 2. To estimate condition of the extraocular muscles. Material and methods: A group of 60 prematurely born children was divided into 2 subgroups: I – 30 children treated with cryotherapy, II – 30 no treatment was applied. All the children had anterior segment, fundus and visual acuity examined. Refraction following cycloplegia was evaluated. Visual acuity and orthoptic status was assessed. Results: In the group of prematurely born children who had retinopathy in the infantile age and were treated with cryotherapy, refractive errors were frequently observed. In over half of those children squint or impaired eye movement were found. In the group of children who required no cryotherapy the percentage of those with refractive errors was similar. Conclusions: In prematurely born children with retinopathy refractive errors and squint occur quite often. Prematurely born children should be subject to ophthalmologic follow-up throughout their childhood.